A new phenotypic classification system for dyslipidemias based on the standard lipid panel - Maureen Sampson (BMC, 2021)
Highlights A new algorithm is described for categorizing dyslipidemic patients into Fredrickson-like lipoprotein phenotypes except for Type III. The new lipoprotein phenotypes were validated by NMR-lipoprotein analysis and by agarose gel electrophoresis/beta-quantification in a large number of subjects. The new lipoprotein phenotyping system identifies high-risk cardiovascular patients and helps direct clinical management. A major advance is that the new lipoprotein phenotypes are based on just the standard lipid panel, and thus can be automatically calculated by the clinical laboratory and widely implemented.